Village Government Strategy in Improving the Economic Independence of the Village Community: A Case Study of Citengah Village. - Gumilar, Budi Gan Gan; Mulyaningsih; Yagus Triana (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
This study aims to analyze the strategy of the Citengah Village government in increasing the economic independence of the community through local economic empowerment. Using descriptive analysis methods and multiple linear regression, this study involved 100 respondents consisting of the community, village officials, and MSME actors. The results of the study showed that MSME training and capital assistance had a significant positive impact on increasing the economic independence of the community. As many as 80% of respondents considered this program to be quite helpful for their economic activities, while the development of economic infrastructure also facilitated access to the market, as expressed by 75% of respondents. Community participation in the planning and implementation of village economic policies was considered very important by 65% ​​of respondents, and was proven to have an effect on the effectiveness of the program. The results of the hypothesis test showed that the village government strategy had a significant effect on the economic independence of the community (p <0.05), and community involvement also had a positive impact (H2 accepted). However, the management of Village Funds has not shown a significant effect (H3 rejected), which indicates challenges in terms of transparency and efficiency of fund use. This study concludes that the village economic empowerment strategy based on community participation and MSME development is effective in increasing economic independence, with recommendations to strengthen the transparency of Village Fund management and expand the marketing network for local products.